Discourse on Religious Moderation in the North Sumatra Baznas Media: Critical Linguistic Analysis Based on the Principles of Maqāṣid al-Sharī'ah - Siregar, Umar Mukhtar (Bahasa Indonesia Prima, 2026)
This study analyzes the discourse of religious moderation constructed in the digital media language of the National Zakat Agency (BAZNAS) of North Sumatra Province, as reflected on its official platform at sumut.baznas.go.id. Using a Critical Discourse Analysis (CDA) approach, this study examines the official posts of BAZNAS North Sumatra for the 2025–2026 period. The evaluative framework of Maqāṣid al-Sharī'ah—which includes safeguarding religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), intellect (ḥifẓ al-'aql), descendants (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl) is used integratively to evaluate the welfare orientation of the discourse practices found. The analysis reveals six main linguistic mechanisms that shape the architecture of BAZNAS North Sumatra's moderation discourse: (1) the naturalization of ideology through the three-element slogan